Prevalence of non-albicans Candida species versus Candida albicans in critical care patients of a tertiary care hospital - Poonam Sharma; Jasvir Kaur; Sarbjeet Sharma (Tropical Journal of Pathology and Microbiology, 2016)
Introduction: Candida species are the most common cause of opportunistic fungal infections. Although C.albicans is most common cause of candidiasis, a shift towards non-albicans Candida species is evident in recent years. The transition of Candida spp. from commensal to a potent pathogen is facilitated by a number of virulence factors viz. adherence to host tissues and medical devices, biofilm formation, and secretion of extracellular hydrolytic enzymes.Objective: To study the prevalence of C.albicans & Non-albicans isolates in critical care settings and determine their virulence factors and antifungal susceptibility profile.Material & Methods: The present study was carried out in the Department of Microbiology, SGRIMSAR, Amritsar during the period of July 2014 to June 2016. Candida strains isolated from various clinical samples received from different ICUs of the hospital were included in the study. The isolates were identified upto species level by both conventional and automated methods (vitek 2 compact system) as per CLSI guidelines. Relevant history of all the patients was taken. They were also screened for the production of virulence factors such as biofilm formation, haemolytic activity, and production of extracellular hydrolytic enzymes i.e. coagulase.Results: Out of the 115 isolates obtained from various ICUs, most common isolate was C. tropicalis 60/115(52.17%) followed by C. albicans 45/115(39.13%), C.utilis 7/115(6.25%). Isolates of C. lusitaniae, C. parasillosis & C. glabrata were 1/115 (0.86%) each. Among these 95/115(82.6%), 75/115(65.2%), and 83/115(72.17%) isolates showed biofilm formation, coagulase production and haemolytic properties respectively.Conclusions: Our study showed a shift among Candida species from albicans (39.13%) to non-albicans (60.86%), thus stressing their presence as major fungal pathogens in critical care settings.